2021
DOI: 10.4236/jep.2021.123011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wastewater Treatment Plants on Retainment of Plastic Microparticles to Enhance Water Quality—A Review

Abstract: Microplastics, plastic pieces of ≤5 mm in size, are ubiquitous in ther environment and can be found in both terrestrial and aquatic ecosystems. This manuscript reviews the literature on the fate of microplastics in wastewater treatment and briefly highlights novel developments in the removal of microplastics from aqueous systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 201 publications
(153 reference statements)
1
7
0
Order By: Relevance
“…Wastewater treatment plants (WWTPs) possess certain sizes of filtering screens that act as a barrier for the microparticles. Also, the size influences the settling behavior of microparticles in settling tanks, e.g., before and after activated sludge treatment (Habib et al 2020b , 2021 ). Usually, smaller-size particles have a higher chance to pass through WWTPs and enter the effluents.…”
Section: Resultsmentioning
confidence: 99%
“…Wastewater treatment plants (WWTPs) possess certain sizes of filtering screens that act as a barrier for the microparticles. Also, the size influences the settling behavior of microparticles in settling tanks, e.g., before and after activated sludge treatment (Habib et al 2020b , 2021 ). Usually, smaller-size particles have a higher chance to pass through WWTPs and enter the effluents.…”
Section: Resultsmentioning
confidence: 99%
“…Recent publications and reviews have reported highly variable concentrations of MPs in effluent sampled from WWTPs [21,27,30,[51][52][53]. A large proportion of the variability and discrepancies observed in these studies can be attributed to the diverse composition of raw wastewater (WW), variations in sampling techniques, isolation and detection methods, and differences in the lower size range considered when isolating and identifying MPs.…”
Section: Microlitter Particle Occurrencementioning
confidence: 99%
“…Meanwhile, household WW content, including litter, is influenced by people's lifestyles, customs, awareness, and the proper use of the sanitation network. Key contributors to microlitter from urban and household sources include fiber losses from textiles during domestic laundering [22][23][24]; microbeads utilized in cosmetics and personal care products like toothpaste, facial cleansers, and body washes [25]; rubber particles produced through the abrasion of tires and carried by stormwater runoff [26,27]; and leachates from landfills [28].…”
Section: Introductionmentioning
confidence: 99%
“…[10,11]; most of these are made from polyethylene (PE) and polypropylene (PP). Polystyrene (PS) products are often used for the manufacture of disposables, such as insulators and food packaging [12,13]; polyethylene terephthalate (PET) is commonly used for the manufacture of containers and packaging in general, among others [14][15][16][17][18]. All such products can be converted into microplastics.…”
Section: Introductionmentioning
confidence: 99%